Vocabulário receptivo de crianças de 2 a 6 anos de idade: uma análise com o Teste de Vocabulário por Imagens Peabody - Tibério, Cinthia Dileine Ruzzante (2017)
The use of the language became deeply consolidated in the human culture, in addition to its use to communicate and share information. The language also has several social and cultural uses, such as identity expression, social stratification, maintenance of the community and entertainment. In this context, there were several studies which aimed to better understand the aspect considered important to assure the success of this ability, the process of the acquisition and development of the language. Our interest in adapting the Peabody Test of Vocabulary through Images to the Brazilian Portuguese raised due to the lack of tools to evaluate the vocabulary in early ages. This test evaluates the receptive vocabulary from two and a half years old up to over 90 years old. The lack of research focused on the extension of the receptive vocabulary of children in Brazilian literature contributed for this research, once in the literature in other countries there are studies referring to this extension. Once this issue is very relevant for the Brazilian education to monitor the amount of receptive vocabulary, this paper aims to determine the extension of the receptive vocabulary in a group of Brazilian children between two and six years old. The Peabody was applied in a private kindergarten school in São Paulo. The sample includes 100 children between two and a half years old and six years old. The results of this study were added and the average and the standard deviation were estimated according to the age and sex separately. An analysis of variance (ANOVA) was conducted in order to determine the influence of the age and sex upon the performance of the Peabody test and Tukey post hoc test to check the evolution of the receptive vocabulary in all ages. The evaluation of the receptive vocabulary with the Peabody test concludes that there is a significant difference in the performance of the Peabody depending on the age. The results indicate that the children had a greater extension of the receptive vocabulary according to their age – the older they were the better results they had. The extension of the vocabulary increased up to five years old, however, there was not a significant difference in the group of children between five and six years old, once the average was very similar. It was also observed that the data revealed there was not a significant difference considering the sex of the children